University Graduates’ Assessment of the Relevance of the Curriculum to the Labor Market in the Philippines - Mae D. Toquero, Cathy; Mae P. Ulanday, Diane (International Research in Education, 2021)
A university with a relevant curriculum offers authentic practical work experience integrated in the subjects to capacitate the graduates to be job-ready to meet the demands of employers in the industry. In contrast, the graduates are confronted with numerous difficulties in finding a job with their acquired that lacks the required skills from degree curriculum. Based on graduates' self assessment report, this study described the match of the educational qualifications and relevance of the curriculum of the graduates to their current employment. A survey research design was used to gather the self-evaluated responses of 1761 individuals who graduated during 2012 to 2017 from the seven colleges of Mindanao State University-General Santos City (MSU-GSC), Philippines. Questionnaires were distributed for data collection through face-to-face and online data gathering. Results revealed that the supply of graduates’ educational skills are highly matched with the skills demanded by the industry and that the curriculum is responsive to the present employment. This research gives implications on academic and economic policies. The university needs to anchor the curriculum evaluation measures to test the graduates’ employability based on a competence model anchored in real-world work settings. The study highlights to conduct a tracer study across the university with a focus on the job-specific skills of the graduates as per degree specialization and evaluate each specific major course based on the prospectus of the program to align MSU-GSC’s course offerings to the needs of the industry.